Retrieval of Emotional Memories. - Buchanan, Tony W. (Psychological Bulletin, 2007)
Long-term memories are influenced by the emotion experienced during learning as well as by the emotion experienced during memory retrieval. The present article reviews the literature addressing the effects of emotion on retrieval, focusing on the cognitive and neurological mechanisms that have been revealed. The reviewed research suggests that the amygdala, in combination with the hippocampus and prefrontal cortex, plays an important role in the retrieval of memories for emotional events. The neural regions necessary for online emotional processing also influence emotional memory retrieval, perhaps through the reexperience of emotion during the retrieval process. Reprinted by permission of the publisher.